2021
DOI: 10.1002/jcb.30196
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of selenium metabolic pathways in cancer: New therapeutic targets for cancer

Abstract: Selenium (Se) is incorporated into the body via the selenocysteine (Sec) biosynthesis pathway, which is critical in the synthesis of selenoproteins, such as glutathione peroxidases and thioredoxin reductases. Selenoproteins, which play a key role in several biological processes, including ferroptosis, drug resistance, endoplasmic reticulum stress, and epigenetic processes, are guided by Se uptake. In this review, we critically analyze the molecular mechanisms of Se metabolism and its potential as a therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 91 publications
(190 reference statements)
0
10
0
Order By: Relevance
“…Additionally, SLITs and ROBOs are involved in anti-tumor activity by regulating chemokine-mediated response in breast cancer; thus, regulation of the expression of SLITs and ROBOs might be associated with chemoresistance [ 37 , 38 , 39 ]. Additionally, other recent studies have demonstrated resistant cancer cells have increased selenocysteine synthesis, which protects cancer cells against oxidative stress [ 40 , 41 , 42 ]. Furthermore, the study by Liu et al showed SRP-dependent co-translational protein targeting to the membrane and amplification of ribosomal protein involved in resistance [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SLITs and ROBOs are involved in anti-tumor activity by regulating chemokine-mediated response in breast cancer; thus, regulation of the expression of SLITs and ROBOs might be associated with chemoresistance [ 37 , 38 , 39 ]. Additionally, other recent studies have demonstrated resistant cancer cells have increased selenocysteine synthesis, which protects cancer cells against oxidative stress [ 40 , 41 , 42 ]. Furthermore, the study by Liu et al showed SRP-dependent co-translational protein targeting to the membrane and amplification of ribosomal protein involved in resistance [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Se has a vast number of promising roles in the human body, including antioxidant, antiinflammatory, and anti-carcinogenic effects that are linked to its incorporation in selenoproteins [23,24]. The role of Se as a potential therapeutic target for cancer was recently reviewed [25]. Humans consume selenium through vegetables, meats, and dietary supplements.…”
Section: The Role Of Elemental Selenium In Selenoproteinsmentioning
confidence: 99%
“…Organoselenium (OSe) compounds have recently gained considerable interest as a potential class of organic motifs due to their outstanding applications in synthetic organic and medicinal chemistry and their possible properties in materials science [ 1 , 2 , 3 , 4 ]. These are attributed to the exceptional properties of the selenium (Se) element.…”
Section: Introductionmentioning
confidence: 99%